2009
DOI: 10.1021/jp908726f
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adsorbed Formate and Oxygen in the Oxidation of Methanol at a Polycrystalline Pt Electrode in 0.1 M KOH: An In Situ Fourier Transform Infrared Study

Abstract: The oxidation of methanol at a polycrystalline Pt anode was investigated with in situ external reflectance Fourier transform infrared (FTIR) spectroscopy in both nitrogen- and oxygen-saturated 0.1 M KOH. The data strongly suggest that adsorbed formate is either the, or at least an important, intermediate in the direct pathway, with attack on this intermediate (rather than its formation) being the rate-determining step. The HCOOads is formed via an Eley−Rideal-type reaction between solution methanol and OHads. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
56
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 40 publications
8
56
0
1
Order By: Relevance
“…In-situ FTIR data at potentials above transition The gain of CO 2 (band at 2340 cm -1 ) clearly shows that the pH, at least in some regions of the thin layer, has fallen below the pK a of carbonic acid, 6.4 [25][31] [32]. However, similar water loss features were observed in our previous studies on methanol oxidation in KOH [31] and attributed to the loss of highly hydrogen-bonded bulk water [45] from the thin layer due to CO 2 gas bubble formation, and this does not seem an unreasonable explanation, particularly given the fact that the other loss features (see table 1) and gain features are observed at both temperatures, suggesting a single mechanism. The formation of acetic acid clearly shows that the pH in the thin layer at these potentials is ≤ 4.7, the pK a of acetic acid 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 [21].…”
Section: (A) and (B) That The Intensities Of The Water O-h Stretch Fesupporting
confidence: 72%
See 2 more Smart Citations
“…In-situ FTIR data at potentials above transition The gain of CO 2 (band at 2340 cm -1 ) clearly shows that the pH, at least in some regions of the thin layer, has fallen below the pK a of carbonic acid, 6.4 [25][31] [32]. However, similar water loss features were observed in our previous studies on methanol oxidation in KOH [31] and attributed to the loss of highly hydrogen-bonded bulk water [45] from the thin layer due to CO 2 gas bubble formation, and this does not seem an unreasonable explanation, particularly given the fact that the other loss features (see table 1) and gain features are observed at both temperatures, suggesting a single mechanism. The formation of acetic acid clearly shows that the pH in the thin layer at these potentials is ≤ 4.7, the pK a of acetic acid 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 [21].…”
Section: (A) and (B) That The Intensities Of The Water O-h Stretch Fesupporting
confidence: 72%
“…As described in our previous papers[25][31][32], at higher potentials during our in-situ FTIR experiments in alkaline solution there is a substantial change in pH in the electrolyte immediately above the electrode and trapped in the thin layer. The swing in pH at higher potentials was ascribed to a combination of[31][32]: (a) relatively slow diffusion of OHions across the electrode surface over a timescale of tens of minutes for an electrode of the radius that we use; and (b) the exhaustion of reactant in the thin electrolyte layer, which leads to further changes in the ambient conditions at the electrode surface. The swing in pH at higher potentials was ascribed to a combination of[31][32]: (a) relatively slow diffusion of OHions across the electrode surface over a timescale of tens of minutes for an electrode of the radius that we use; and (b) the exhaustion of reactant in the thin electrolyte layer, which leads to further changes in the ambient conditions at the electrode surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In alkaline medium the reaction routes and product distribution alter due to the change in the work function of the electrode material: the main products on a polycrystalline Pt electrode [ 64 ] are formate (formic acid in alkaline medium dissociates rapidly to formate ion − HCOO ) and bicarbonate ( − 3 HCO ) in the low potential region (> 0.2 V) as well as CO 2 above a potential of 0.7 V. On Pt(111) electrode [65] the main products are formate and CO 2 . According to DFT calculation the electrocatalytic activity of Pd on alcohol oxidation is strongly depended on pH [66] and at high pH solutions Pd could be an alternative for Pt.…”
Section: Methanolmentioning
confidence: 99%
“…9 Christensen et al have shown that the interfacial pH drops at higher potentials due to the high consumption of OH -which is not completely counterbalanced by the OH -diffusion from the bulk-phase. [10][11][12] This phenomenon leads to a transition from alkaline to acidic conditions at the interphase. The transition potential varies with the diffusion rate of OH -which is dependent on the temperature and mass flow-rate.…”
Section: Introductionmentioning
confidence: 99%